ORGANIC GEOCHEMISTRY OF THE ABALAK FORMATION OF THE WEST-SIBERIAN PETROLEUM BASIN - Kontorovich A.E.; Danilova V.P.; Kostyreva E.A.; Melenevskii V.N.; Gilinskaya L.G.; Levchuk M.A.; Moskvin V.I.; Fomin A.N.; Yudina N.T. (My University, 2000)
Geochemistry of dispersed organic matter (DOM) from oil source rocks of the Abalak Formation and Lower-Vasyugan Subformation of the West-Siberian Plate is considered on a new information level. Regularities of distribution of iron forms, organic carbon, its isotopic composition, pyrolytic characteristics, and thermal maturity of the DOM were studied in these deposits. Geochemistry of bitumens from the DOM of the Abalak Formation and Lower-Vasyugan Subformation was examined in detail at the molecular level. A wide spectrum of biomarker hydrocarbons and specific features of their distribution have been established. The organic matter from the deposits studied has been shown to be of mixed nature with a predominance of higher-rank land plants. The proportion of terrestrial OM is much greater in the Lower-Vasyugan Subformation than in the Abalak Formation. According to depths of occurrences of the Abalak Formation and Lower-Vasyugan Subformation in the study area, organic matter from the subformation showed a higher level of thermal maturity. Based on comparison of biomarker-hydrocarbon distribution in the above strata with that of the West-Siberian oils, it was suggested that, in spite of their definite intrinsic haphthide-generative potential, they were not oil-generating.